LIQUID CHROMATOGRAPHY MASS SPECTROMETRY PROFILING AND ANTIMICROBIAL ACTIVITIES OF THE METHANOLIC FRACTION OF CRINUM JAGUS RHIZOME FOUND IN DUTSIN-MA - Salsabilu, Kabir; Ali, Tijjani; Bello, Oluwasesan M.; Gafar, Maryam Kemi (FUDMA JOURNAL OF SCIENCES, 2025)
Rhizome of Crinum jagus was investigated to identify chemical substances of medicinal value to enable scientific validation of the plant in the treatment of pathogenic microorganisms’ related diseases. The plant’s rhizome, was subjected to cold extraction using methanol. The extract obtained was subjected to phytochemical screening, antimicrobial activities and liquid chromatography mass spectrometry analyses using standard procedures. The preliminary phytochemical screening of the crude extract revealed the presence of flavonoids, tannins, glycosides, steroids, triterpenoids, saponins and alkaloids. The Antimicrobial effects of the crude extract were tested against nine microorganisms namely: Bacillus magisterium, Staphylococcus aureus, Streptococcus pneumonia, Escherichia coli, Salmonella typhi, Pseudomonas aeruginosa, Candida albicans Trichophyton rubrum and Aspergillus niger. The antimicrobial activities indicates that, the extract possess significant activity against Staphylococcus aureus (Zone of inhibition ranged from 09mm to 26mm at MIC ranges: 200 mg/ml). The result of the LCMS analysis of methanolic fraction revealed the presence of molecular fragmentation patterns at m/z 512.287. The findings of this research suggest the presence of a compound(s) with a parent molecular ion around 512, possibly indicating a molecular formula near C₃0H50O or similar, characteristic of triterpenoids. The phytochemical constituent’s and antimicrobial assay indicate that the plant could be used in the treatment of microorganisms related diseases.
Keywords: Antimicrobial; Chromatography; Fraction; Methanolic; Rhizome